2020
DOI: 10.1016/j.jconrel.2020.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA from the lab discovery to patients' recovery

Abstract: In 1998, the RNA interference discovery by Fire and Mello revolutionized the scientific and therapeutic world. They showed that small double-stranded RNAs, the siRNAs, were capable of selectively silencing the expression of a targeted gene by degrading its mRNA. Very quickly, it appeared that the use of this natural mechanism was an excellent way to develop new therapeutics, due to its specificity at low doses. However, one major hurdle lies in the delivery b) SNALP .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 130 publications
0
41
0
Order By: Relevance
“…Kim et al [ 16 ] reported that hydrophobic quantum dots (QDs) [ 17 ] were effectively incorporated into lipid bilayers, and then therapeutic short-interfering RNAs (siRNAs) [ 18 ] were complexed with QD-lipid nanocarriers (QLs). Anti-epidermal growth factor receptor [ 19 ] (EGFR) aptamer-lipid conjugates were inserted into the QLs for triple-negative breast cancer (TNBC) targeting.…”
Section: Targeted Deliverymentioning
confidence: 99%
“…Kim et al [ 16 ] reported that hydrophobic quantum dots (QDs) [ 17 ] were effectively incorporated into lipid bilayers, and then therapeutic short-interfering RNAs (siRNAs) [ 18 ] were complexed with QD-lipid nanocarriers (QLs). Anti-epidermal growth factor receptor [ 19 ] (EGFR) aptamer-lipid conjugates were inserted into the QLs for triple-negative breast cancer (TNBC) targeting.…”
Section: Targeted Deliverymentioning
confidence: 99%
“…Typically, cationic lipids, such as N -[1-(2,3-dioleyloxy)propyl]-n,n,n-trimethylammonium chloride (DOTMA) and 1,2-dioleoyl-3-trimethylammonium-propane chloride salt (DOTAP), are used to form lipoplexes with, or encapsulate, RNA [ 36 ]. The addition of neutral helper lipids, such as dioleoyl phosphatidylethanolamine (DOPE) and cholesterol, in the lipoplexes provide the ability to facilitate RNA complexation, increase stability of the lipoplexes, and reduce toxicity [ 37 , 38 ]. One major problem associated with lipid-based systems for pulmonary delivery is their poor structural stability because they readily fuse with pulmonary surfactants in the airways [ 39 ], leading to premature release of RNA before cellular uptake.…”
Section: Rna Delivery Vectors For Pulmonary Deliverymentioning
confidence: 99%
“…One of the most studied and recognized sphere of CLs application is their use for transfection. Their positive charge makes them an exceptional nanocarrier for negatively charged nucleic acid sequences and is advantageous due to higher tissue uptake and endosomal escape capabilities [ 198 ]. For a few decades, cationic liposomes have attracted attention due to their lower immunogenicity, little to no toxicity, when biodegradable lipids are used, and they have since been studied thoroughly to be used in transfection [ 199 ].…”
Section: Self-assembled Amphiphilic Systems As Smart Drug Nanocarrmentioning
confidence: 99%
“…For a few decades, cationic liposomes have attracted attention due to their lower immunogenicity, little to no toxicity, when biodegradable lipids are used, and they have since been studied thoroughly to be used in transfection [ 199 ]. Thus, scientific interest in CLs for transfection has not dwindled in the past few years [ 198 , 200 , 201 , 202 , 203 , 204 ]. Another major field of CL application is their use as vaccine adjuvants due to their ability to protect the delivered vaccine, retain it at the injection site, and some degree of immunostimulation [ 205 , 206 ].…”
Section: Self-assembled Amphiphilic Systems As Smart Drug Nanocarrmentioning
confidence: 99%